2017
DOI: 10.1088/1361-6382/aa60eb
|View full text |Cite
|
Sign up to set email alerts
|

Globally coherent short duration magnetic field transients and their effect on ground based gravitational-wave detectors

Abstract: Abstract. It has been recognized that the magnetic fields from the Schumann resonances could affect the search for a stochastic gravitational-wave background by LIGO and Virgo. Presented here are the observations of short duration magnetic field transients that are coincident in the magnetometers at the LIGO and Virgo sites. Data from low-noise magnetometers in Poland and Colorado, USA, are also used and show short duration magnetic transients of global extent. We measure at least 2.3 coincident (between Polan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 48 publications
(97 reference statements)
0
36
0
Order By: Relevance
“…Observations of ELF sferic waveforms are made near Hugo, Colorado, USA (38.9 ∘ N, 103.4 ∘ W), and Hylaty, Poland (49.2 ∘ N, 22.5 ∘ E), using ELA10 receivers described by Kulak et al (2014) with sampling frequency of 888 Hz. Due to their sensitivity and electromagnetically quiet locations, these receivers have been used not only for lightning and ionospheric investigations but also in identification of electromagnetic perturbations in gravitational wave observations (Coughlin et al, 2016;Kowalska-Leszczynska et al, 2017). For lightning discharge locations we use the Global Lightning Dataset (GLD360; Said et al, 2013Said et al, , 2010.…”
Section: Observationsmentioning
confidence: 99%
“…Observations of ELF sferic waveforms are made near Hugo, Colorado, USA (38.9 ∘ N, 103.4 ∘ W), and Hylaty, Poland (49.2 ∘ N, 22.5 ∘ E), using ELA10 receivers described by Kulak et al (2014) with sampling frequency of 888 Hz. Due to their sensitivity and electromagnetically quiet locations, these receivers have been used not only for lightning and ionospheric investigations but also in identification of electromagnetic perturbations in gravitational wave observations (Coughlin et al, 2016;Kowalska-Leszczynska et al, 2017). For lightning discharge locations we use the Global Lightning Dataset (GLD360; Said et al, 2013Said et al, , 2010.…”
Section: Observationsmentioning
confidence: 99%
“…The potential for the contamination of searches for a SGWB is strong due to potential correlated environmental noise between detectors [5,[7][8][9][10][11], which would result in a systematic error in the searches. A related concern exists in searches for transient sources of gravitational waves, such as due to correlated magnetic transients from storms [12].…”
Section: Introductionmentioning
confidence: 99%
“…The two Advanced LIGO detectors are separated by 3000 km. However, even with substantial separation it has been demonstrated that global magnetic field noise from the Schumann resonances can have a coherence between the LIGO and Virgo sites [25,26]. For this present study we will ignore these magnetic field correlations.…”
Section: B Sensitivity Limit ωGw(f )mentioning
confidence: 99%